Photobleaching of YOYO-1 in super-resolution single DNA fluorescence imaging - Pyle, Joseph R.; Chen, Jixin (Beilstein Journal of Nanotechnology, 2017)
Super-resolution imaging of single DNA molecules via point accumulation for imaging in nanoscale topography (PAINT) has great potential to visualize fine DNA structures with nanometer resolution. In a typical PAINT video acquisition, dye molecules (YOYO-1) in solution sparsely bind to the target surfaces (DNA) whose locations can be mathematically determined by fitting their fluorescent point spread function. Many YOYO-1 molecules intercalate into DNA and remain there during imaging, and most of them have to be temporarily or permanently fluorescently bleached, often stochastically, to allow for the visualization of a few fluorescent events per DNA per frame of the video. Thus, controlling the fluorescence on–off rate is important in PAINT. In this paper, we study the photobleaching of YOYO-1 and its correlation with the quality of the PAINT images. At a low excitation laser power density, the photobleaching of YOYO-1 is too slow and a minimum required power density was identified, which can be theoretically predicted with the proposed method in this report.
Keywords: diffusion; PAINT; single-molecule photophysics; super-resolution imaging

(untitled) - Lopez, S. G.; Ruedas-Rama, M. J.; Casares, S.; Alvarez-Pez, J. M.; Orte, A. (J. Phys. Chem. B, 2012)

(untitled) - Talavera, E. M.; Bermejo, R.; Crovetto, L.; Orte, A.; Alvarez-Pez, J. M. (Appl. Spectrosc., 2003)

(untitled) - Idziorek, T.; Estaquier, J.; De Bels, F.; Ameisen, J.-C. (J. Immunol. Methods, 1995)

(untitled) - Michel, A. D.; Kaur, R.; Chessell, I. P.; Humphrey, P. P. A. (Br. J. Pharmacol., 2000)

(untitled) - Eriksson, M.; Härdelin, M.; Larsson, A.; Bergenholtz, J.; Åkerman, B. (J. Phys. Chem. B, 2007)

(untitled) - Matsuura, S.; Komatsu, J.; Hirano, K.; Yasuda, H.; Takashima, K.; Katsura, S.; Mizuno, A. (Nucleic Acids Res., 2001)

(untitled) - Xu, C.; Losytskyy, M. Y.; Kovalska, V. B.; Kryvorotenko, D. V.; Yarmoluk, S. M.; McClelland, S.; Bianco, P. R. (J. Fluoresc., 2007)

(untitled) - Reisner, W.; Larsen, N. B.; Silahtaroglu, A.; Kristensen, A.; Tommerup, N.; Tegenfeldt, J. O.; Flyvbjerg, H. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Nilsson, A. N.; Emilsson, G.; Nyberg, L. K.; Noble, C.; Stadler, L. S.; Fritzsche, J.; Moore, E. R. B.; Tegenfeldt, J. O.; Ambjörnsson, T.; Westerlund, F. (Nucleic Acids Res., 2014)

(untitled) - Baday, M.; Cravens, A.; Hastie, A.; Kim, H.; Kudeki, D. E.; Kwok, P.-Y.; Xiao, M.; Selvin, P. R. (Nano Lett., 2012)

(untitled) - Tian, N.; Xu, Q.-H. (Adv. Mater., 2007)

(untitled) - Flors, C. (Photochem. Photobiol. Sci., 2010)

(untitled) - Rye, H. S.; Yue, S.; Wemmer, D. E.; Quesada, M. A.; Haugland, R. P.; Mathies, R. A.; Glazer, A. N. (Nucleic Acids Res., 1992)

(untitled) - Netzel, T. L.; Nafisi, K.; Zhao, M.; Lenhard, J. R.; Johnson, I. (J. Phys. Chem., 1995)

(untitled) - Fürstenberg, A.; Julliard, M. D.; Deligeorgiev, T. G.; Gadjev, N. I.; Vasilev, A. A.; Vauthey, E. (J. Am. Chem. Soc., 2006)

(untitled) - Selvin, P. (Science, 1992)

(untitled) - Flors, C.; Ravarani, C. N. J.; Dryden, D. T. F. (ChemPhysChem, 2009)

(untitled) - Persson, F.; Bingen, P.; Staudt, T.; Engelhardt, J.; Tegenfeldt, J. O.; Hell, S. W. (Angew. Chem., Int. Ed., 2011)

(untitled) - Miller, H.; Zhou, Z.; Wollman, A. J. M.; Leake, M. C. (Methods, 2015)

(untitled) - Schoen, I.; Ries, J.; Klotzsch, E.; Ewers, H.; Vogel, V. (Nano Lett., 2011)

(untitled) - Biteen, J.; Willets, K. A. (Chem. Rev., 2017)

(untitled) - Vilar, J. M. G.; Saiz, L. (Curr. Opin. Genet. Dev., 2005)

(untitled) - Jungmann, R.; Steinhauer, C.; Scheible, M.; Kuzyk, A.; Tinnefeld, P.; Simmel, F. C. (Nano Lett., 2010)

(untitled) - Rajendran, A.; Endo, M.; Hidaka, K.; Sugiyama, H. (Angew. Chem., Int. Ed., 2014)

(untitled) - Ortega-Esteban, A.; Bodensiek, K.; San Martín, C.; Suomalainen, M.; Greber, U. F.; de Pablo, P. J.; Schaap, I. A. T. (ACS Nano, 2015)

(untitled) - Hell, S. W.; Wichmann, J. (Opt. Lett., 1994)

(untitled) - Blom, H.; Widengren, J. (Chem. Rev., 2017)

(untitled) - von Diezmann, A.; Shechtman, Y.; Moerner, W. E. (Chem. Rev., 2017)

(untitled) - Liu, S.; Cao, K.; Li, H.; Song, J.; Han, J.; Shen, Y.; Wang, M. (Sol. Energy, 2017)

(untitled) - Lee, A.; Tsekouras, K.; Calderon, C.; Bustamante, C.; Pressé, S. (Chem. Rev., 2017)

(untitled) - Sydor, A. M.; Czymmek, K. J.; Puchner, E. M.; Mennella, V. (Trends Cell Biol., 2015)

(untitled) - Rust, M. J.; Bates, M.; Zhuang, X. (Nat. Methods, 2006)

(untitled) - Betzig, E.; Patterson, G. H.; Sougrat, R.; Lindwasser, O. W.; Olenych, S.; Bonifacino, J. S.; Davidson, M. W.; Lippincott-Schwartz, J.; Hess, H. F. (Science, 2006)

(untitled) - Gordon, M. P.; Ha, T.; Selvin, P. R. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Sharonov, A.; Hochstrasser, R. M. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Molle, J.; Raab, M.; Holzmeister, S.; Schmitt-Monreal, D.; Grohmann, D.; He, Z.; Tinnefeld, P. (Curr. Opin. Biotechnol., 2016)

(untitled) - Cox, S.; Rosten, E.; Monypenny, J.; Jovanovic-Talisman, T.; Burnette, D. T.; Lippincott-Schwartz, J.; Jones, G. E.; Heintzmann, R. (Nat. Methods, 2012)

(untitled) - van de Linde, S.; Sauer, M. (Chem. Soc. Rev., 2014)

(untitled) - Åkerman, B.; Tuite, E. (Nucleic Acids Res., 1996)

(untitled) - Kanony, C.; Åkerman, B.; Tuite, E. (J. Am. Chem. Soc., 2001)

(untitled) - Tycon, M. A.; Dial, C. F.; Faison, K.; Melvin, W.; Fecko, C. J. (Anal. Biochem., 2012)

(untitled) - Carlsson, C.; Johnson, M.; Åkerman, B. (Nucleic Acids Res., 1995)

(untitled) - Chen, J.; Bremauntz, A.; Kisley, L.; Shuang, B.; Landes, C. F. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Kisley, L.; Chen, J.; Mansur, A. P.; Shuang, B.; Kourentzi, K.; Poongavanam, M.-V.; Chen, W.-H.; Dhamane, S.; Willson, R. C.; Landes, C. F. (Proc. Natl. Acad. Sci. U. S. A., 2014)

(untitled) - Shuang, B.; Chen, J.; Kisley, L.; Landes, C. F. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Ke, C.-S.; Fang, C.-C.; Yan, J.-Y.; Tseng, P.-J.; Pyle, J. R.; Chen, C.-P.; Lin, S.-Y.; Chen, J.; Zhang, X.; Chan, Y.-H. (ACS Nano, 2017)

(untitled) - Hou, L.; Adhikari, S.; Tian, Y.; Scheblykin, I. G.; Orrit, M. (Nano Lett., 2017)

(untitled) - Chen, T.-Y.; Santiago, A. G.; Jung, W.; Krzemiński, Ł.; Yang, F.; Martell, D. J.; Helmann, J. D.; Chen, P. (Nat. Commun., 2015)

(untitled) - Janssen, D.; De Palma, R.; Verlaak, S.; Heremans, P.; Dehaen, W. (Thin Solid Films, 2006)

(untitled) - Han, Y.; Mayer, D.; Offenhäusser, A.; Ingebrandt, S. (Thin Solid Films, 2006)

(untitled) - Fiorilli, S.; Rivolo, P.; Descrovi, E.; Ricciardi, C.; Pasquardini, L.; Lunelli, L.; Vanzetti, L.; Pederzolli, C.; Onida, B.; Garrone, E. (J. Colloid Interface Sci., 2008)

(untitled) - Krishnamoorthy, G.; Duportail, G.; Mély, Y. (Biochemistry, 2002)

(untitled) - Thompson, R. E.; Larson, D. R.; Webb, W. W. (Biophys. J., 2002)

(untitled) - Simonson, P. D.; Rothenberg, E.; Selvin, P. R. (Nano Lett., 2011)

(untitled) - Rosten, E.; Jones, G. E.; Cox, S. (Nat. Methods, 2013)

(untitled) - Zhu, L.; Zhang, W.; Elnatan, D.; Huang, B. (Nat. Methods, 2012)

(untitled) - Dertinger, T.; Colyer, R.; Iyer, G.; Weiss, S.; Enderlein, J. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Kisley, L.; Brunetti, R.; Tauzin, L. J.; Shuang, B.; Yi, X.; Kirkeminde, A. W.; Higgins, D. A.; Weiss, S.; Landes, C. F. (ACS Nano, 2015)

(untitled) - Wang, W.; Shen, H.; Shuang, B.; Hoener, B. S.; Tauzin, L. J.; Moringo, N. A.; Kelly, K. F.; Landes, C. F. (J. Phys. Chem. Lett., 2016)